2002
DOI: 10.1159/000065454
|View full text |Cite
|
Sign up to set email alerts
|

Hyperphosphatemia Modestly Retards Parathyroid Hormone Suppression during Calcitriol-Induced Hypercalcemia in Normal and Azotemic Rats

Abstract: Background/Aims: In in vitro studies, a high phosphate concentration has been shown to directly stimulate parathyroid hormone (PTH) secretion in a normal calcium concentration and to reduce PTH suppression in a high calcium concentration. In hemodialysis patients during dialysis-induced hypercalcemia, the effect of hyperphosphatemia on PTH secretion was less than in vitro studies. Our goal was to determine whether hyperphosphatemia retards PTH suppression during calcitriol-induced hypercalcemia in azotemic rat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
1

Year Published

2003
2003
2005
2005

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 36 publications
0
0
1
Order By: Relevance
“…21 On the other hand, a recent in vivo study revealed that such an effect of phosphate was rather small. 22 In the present study, the effect of maxacalcitol therapy was not predictable by pretreatment Pi levels. Because the pretreatment Pi levels may not have represented the Pi levels throughout the observation period, we do not insist, from this result, that serum Pi levels have no effect on parathyroid function.…”
Section: Fig 3a-ccontrasting
confidence: 57%
“…21 On the other hand, a recent in vivo study revealed that such an effect of phosphate was rather small. 22 In the present study, the effect of maxacalcitol therapy was not predictable by pretreatment Pi levels. Because the pretreatment Pi levels may not have represented the Pi levels throughout the observation period, we do not insist, from this result, that serum Pi levels have no effect on parathyroid function.…”
Section: Fig 3a-ccontrasting
confidence: 57%